Effects of High-Power Diode Laser Irradiation Combined with Electrical Stimulation on Wrist Pain and Function Following Carpal Tunnel Syndrome - Tabatabai, Seyed Mohammad Reza; Bashardoust Tajali, Siamak; Attarbashi Moghadam, Behrooz; Mir, Seyed Mohsen (Journal of Clinical Physiotherapy Research, 2016)
Introduction: Carpal Tunnel Syndrome (CTS) is the most common and most well-known compression neuropathy which may manifest as mild, moderate, or severe and lead to various degrees of disability in people. The present study aimed to compare the effect of high-power diode laser beam and Transcutaneous Electrical Nerve Stimulation (TENS) separately and in combination on improvement of wrist pain and function in patients with CTS. Method and Materials: The study was designed as a randomized trial. A total of 45 patients (7 men and 38 women) were randomly divided into three groups of high-power laser (n=15), TENS (n=15), and high-power laser with TENS (n=15). The TENS group received conventional TENS on pain site for two weeks as 5 sessions per week and 30 minutes per session. The high-power laser group received 6.5 J/cm2 laser for two weeks, 5 sessions per week. The group of high-power laser with TENS received conventional TENS and then 6.5 J/cm2 laser for two weeks as 5 sessions per week and 30 minutes per session. The Persian McGill Pain Questionnaire, Visual Analogue Scale (VAS), and the 5-point scale of pain severity of McGill Pain Questionnaire (pain severity) were used to assess pain and the Persian version of the Disabilities of Arm, Shoulder, and Hand (DASH) questionnaire was administered to evaluate hand function before and after treatment. All the patients filled a demographic questionnaire including age, height, and weight prior to the intervention. Results: The mean scores of McGill, VAS, pain severity, and DASH questionnaires reduced significantly in high-power laser and high-power laser with TENS groups; however, these variables had no significant difference in the TENS group. Conclusions: High-power laser diode (808 nm, 6.5 j/cm2) can reduce pain and improve hand function in patients with mild to moderate CTS. Laser-induced anti-inflammatory effects and blood flow improvement are possible causes of decreased pain and sensory signs followed by improvement in hand function. Key words: Carpal Tunnel Syndrome, High-Power Laser, Hand, Pain, Transcutaneous Electrical Nerve Stimulation